2013
DOI: 10.1016/j.apt.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of medical-grade stainless steel powders prepared by mechanical alloying and subsequent annealing

Abstract: a b s t r a c tThe harmful effect of nickel ions released from conventional stainless steel implants has provided a high level of motivation for the further development of nickel-free stainless steels. In this paper, the microstructure of medical-grade nickel-free stainless steel powders, with the chemical composition of ASTM F2581, is studied during mechanical alloying and subsequent annealing. Rietveld X-ray diffraction and transmission electron microscopy evaluations reflect nanocrystallization, austenitiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The other furnacecooled samples showed a magnetic response, so they were far from being fully austenite. The amorphization process also influences the magnetic behaviour, since the formation of this phase delays the ferrite-austenite transformation [29]. This phenomenon is of consideration for milling times as long as 72 and 96 h.…”
Section: Phase Identification By Magnetism and Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The other furnacecooled samples showed a magnetic response, so they were far from being fully austenite. The amorphization process also influences the magnetic behaviour, since the formation of this phase delays the ferrite-austenite transformation [29]. This phenomenon is of consideration for milling times as long as 72 and 96 h.…”
Section: Phase Identification By Magnetism and Xrd Analysismentioning
confidence: 99%
“…The powders obtained by MA are a different alternative which is explored in this work. In this sense, Salahinejad et al demonstrated the interest of mechanical alloying and subsequent annealing in the development of nanostructured medical-grade SS [29].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the structure and some properties of powder metallurgy (mechanical alloying and liquid-phase sintering) samples with the latter standard composition were investigated. 21,22,23 Typically, it was found that a higher resistance to uniform corrosion, estimated from EIS experiments, dictates a more cell viability on the surfaces, albeit when liquid-phase sintering was completely activated. 10 Nevertheless, the question is whether this conclusion is universal, i.e.…”
mentioning
confidence: 99%
“…The solute drag effect combined with the contribution of carbon and nitrogen are expected to be responsible for the retarded grain growth in this material. The solubility of nitrogen and carbon atoms in crystals is limited; therefore, they segregate at grain boundaries [16][17][18] and retard grain boundary mobility at high temperatures [18][19][20][21]. can be seen, both increases by increasing the sintering aid content, due to the progress in densification and the decrease of retained porosity.…”
Section: Resultsmentioning
confidence: 95%